Non profit institutions IT governance: Private high education institutions in bogota case - Muriel-Perea, Yasser de Jesús; Díaz Piraquive, Flor Nancy; González-Crespo, Rubén; Rozo-Rojas, Ivanhoe (Communications in Computer and Information Science, KMO 2017, 2020)
Higher Education institutions (HEI) and non-profit institutions are relevant in the education sector because they can create a private and public value. In fact, to a great extent, the development of a country is linked to its education and therefore to the HEIs, which are the ones that provide it. There are several studies that correlate the performance of business organizations with their governance about information technology (IT). These research works have been developed mainly in profit companies, using ROI and ROA as measures of performance, indicators that do not apply to non-profit entities, such as HEIs, which are measured through benefit and social impact indicators. Therefore, this research analysed IT governance in some private non-profit institutions from Colombia, with the purpose of identifying the current state of its practices in the subject, and the correlation that exists between the IT government and its performance. The method used was the consultation of experts of the HEIs studied, identification of the IT governance profile, design of a performance matrix and the location of HEIs. The conclusions obtained reflect the importance of the good practices analysed by the IT government in the HEIs studied, which have not yet been capitalized to improve both academic and administrative performance; therefore, it will strengthen innovative practices, aimed at the delivery of quality education, which can be evaluated with indicators of impact, social benefit and project management.
Conferencia de "12th International Conference on Knowledge Management in Organizations, KMO 2017; Beijing; China; 21 August 2017 through 24 August 2017"
Keywords: IT governance; operational model; IT governance mechanisms; IT portfolio; higher education institutions; HEI; private in Bogotá; HEI performance; Scopus(2); WOS(2)